Development of a rapid and accurate CRISPR/Cas13-based diagnostic test for GII.4 norovirus infection - Duan, Lei; Yang, Xiaohan; Zhan, Wenli; Tang, Yuan; Wei, Mengru; Chen, Keyi; Liu, Pan; Xie, Jia; Zhang, Changbin; Zhao, Hongyu; Luo, Mingyong (Frontiers in Microbiology, 2022)
Genogroup II genotype 4 (GII.4) norovirus causes acute gastroenteritis in children, and its infection is more severe than that of other genotypes. Early and precise detection and treatment are critical for controlling its spread and reducing the severity of infection. In this study, a rapid and efficient isothermal assay for the GII.4 norovirus detection (GII.4-CRISPR detection) was developed based on the CRISPR/Cas13a system. The assay can be applied without expensive instrumentation, and the results can be read via both fluorescence and lateral flow strip (LFS). The analytical sensitivity of this assay was 5 copies/reaction, and there was no cross-reaction with other genotypes of norovirus or other clinically common pathogens. There was a coincidence rate of 100% between our assay and commercial quantitative polymerase chain reaction. GII.4-CRISPR detection improves upon the shortcomings of some previously established molecular methods of detection, particularly with regard to accessibility. It provides an alternative tool for outbreak control and early diagnosis of GII.4 norovirus infection.